The Science of Memory Loss: Insights into Alzheimer’s Disease - Starzyk, Agnieszka; Charzewski, Piotr (Quality in Sport, 2025)
Alzheimer’s disease (AD), the leading cause of dementia, is a growing public health crisis and one of the most burdensome diseases of the 21st century. Since the 2016 Seminar, substantial progress has been made in understanding AD’s complex pathogenesis, identifying genetic risk and protective factors, and developing novel diagnostic biomarkers and therapeutic strategies. This review synthesizes findings from recent studies sourced from PubMed and Embase, focusing on advances in cerebrospinal fluid and blood-based biomarkers, imaging techniques such as PET and MRI, and therapeutic interventions. Current pharmacological treatments, including cholinesterase inhibitors and NMDA receptor antagonists, provide only symptomatic relief and fail to alter disease progression. Emerging therapies, such as monoclonal antibodies targeting amyloid-beta and tau proteins, show promise but are hindered by challenges in efficacy and safety. Neuroinflammation, driven by cytokines like IL-1β and TNF-α, is increasingly recognized as a central contributor to AD pathology, offering new therapeutic targets. Lifestyle modifications and multidomain prevention strategies, including exercise, cognitive training, and diet, demonstrate potential in reducing cognitive decline, particularly in at-risk populations. Despite these advancements, the development of effective disease-modifying treatments remains a pressing challenge. Continued innovations in biomarker research, therapeutic approaches, and personalized medicine are essential to improve outcomes for individuals with AD and to mitigate its growing societal impact.